(untitled) (Research, Society and Development, 2024)
This study aims to analyze the socioeconomic profile of producers in Patos de Minas and evaluate access to Rural Credit in the region. The research used primary information obtained through questionnaires applied to producers throughout 2022. Data analysis was performed using the statistical software StataMP 17. The results reveal that most of the producers have a high level of education and are in an advanced age group. With regard to Rural Credit, almost all producers in the region are beneficiaries of this policy, which is essentially aimed at investments and funding. These findings highlight the relevance of Rural Credit as a crucial tool for sustaining and developing agricultural activities in the region, providing the necessary resources for improvements and innovations in rural properties. In addition, the high level of education of producers suggests a potential for the adoption of more efficient and sustainable agricultural practices. However, the advanced age of producers may indicate the need for policies aimed at family succession and the attraction of young people to rural activity, ensuring the continuity of the agricultural sector in the region.